The Apitan Tradition of Maintaining Harmony and Friendship : A Study of Living Hadith in Tlogorejo Village, Karangawen, Demak - Afifah; Muhammad Kudhori; Umi Bariroh (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the Apitan tradition as a form of Living Hadith in the social life of the people of Tlogorejo Village, Karangawen District, Demak Regency. This tradition is carried out every month of Dzulqa'dah as a form of gratitude for a safe and peaceful village, an abundance of sustenance, and as a means of strengthening friendship and maintaining harmony between residents. Using a descriptive qualitative approach and the hadith living method, this study highlights how Saw's prophetic values such as ukhuwah, social concern, and spiritual education are internalized in local cultural practices. In contrast to similar traditions in other areas that are colored by puppet performances, Apitan in Tlogorejo is filled with public recitation and tambourine performances as a form of adaptation to Islamic values. The results of the study show that the Apitan tradition has a significant impact on the social, religious, cultural, economic, and educational aspects of the community. This tradition is not only the preservation of culture, but also a means of actualizing the values of the hadith that are alive and developing in the local context. Thus, Apitan reflects a harmonious meeting between religion and culture that is able to strengthen the Islamic identity of the community within the framework of local wisdom.